2007
DOI: 10.1111/j.1440-1681.2007.04681.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant, but Not Antiepileptic, Action of Valproate on Audiogenic Seizures in Metaphit–treated Rats

Abstract: 1. The blocking effects of valproate (2-propylpentanoic acid), a standard anti-epileptic drug, on metaphit (1-[1-(3-isothiocyanatophenyl)-cyclohexyl]-piperidine)-induced audiogenic seizures as a model of generalized, reflex audiogenic epilepsy in adult Wistar male rats were studied. 2. Rats were stimulated using an electric bell (100 +/- 3 dB, 5-8 kHz, 60 s) 60 min after i.p. metaphit (10 mg/kg) injection and afterwards at hourly intervals. For power spectra and electroencephalograph (EEG) recordings, three go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, the drug did not exhibit significant effect on electrocortical activity. So, they concluded that valproate is an anticonvulsant rather than antiepileptic drug [ 62 ]. By comparison, it may be suggested that TCS OX2 29 had a higher potency than valproate.…”
Section: Discussionmentioning
confidence: 99%
“…However, the drug did not exhibit significant effect on electrocortical activity. So, they concluded that valproate is an anticonvulsant rather than antiepileptic drug [ 62 ]. By comparison, it may be suggested that TCS OX2 29 had a higher potency than valproate.…”
Section: Discussionmentioning
confidence: 99%
“…Modelling the epileptic activity in animals involves two main approaches: administering different chemical compounds and electrical stimulation kindling. In our Laboratory for Neurophysiology, different animal models have been developed, including metaphit audiogenic seizures (18)(19)(20)(21) and lindane- (22)(23)(24) and homocysteine thiolactoneinduced seizures (11). In addition to these models, the other commonly used experimental epilepsy models are those induced by factors such as N-methyl-D-aspartate (NMDA), pentylenetetrazol, pilocarpine, kainic acid, and 4-aminopyridine amygdala kindling (for review see 4).…”
Section: Modelling Of Epileptic Activity In Animals: Unique Features mentioning
confidence: 99%
“…The generative and regulatory processes of both systems (bottom-up and top-down) are closely interdependent and overlap in neural processes that are in constant interaction. By experimental research on animal models and using the method of neurophysiological lesions, specific cortical and subcortical neural networks have been identified as a biological substrate for emotions [33,50,51]. Emotion regulation and control arise as a complex process in a network of neural groups that mediate cognitive, emotional and behavioral functions (the prefrontal cortex, limbic, and temporal regions).…”
Section: Neurophysiological Determinants Of Emotions (Bottom-up Vs Top-down)mentioning
confidence: 99%